On the matching method and the Goldstone theorem in holography - Bajc, Borut (2013)
We study the transition of a scalar field in a fixed AdS (d+1) background between an extremum and a minimum of a potential. We compute analytically the solution to the perturbation equation for the vev deformation case by generalizing the usual matching method to higher orders and find the propagator of the boundary theory operator defined through the AdS-CFT correspondence. We show that, contrary to what happens at the leading order of the matching method, the next-to-leading order presents a simple pole at q (2) = 0 in accordance with the Goldstone theorem applied to a spontaneously broken dilatation invariance.